The effects of stretching on strength performance - Rubini, E. C.; Costa, A. L. L.; Gomes, P. S. C. (Sports Medicine, 2007)
Strength and flexibility are common components of exercise programmes; however, it is not clear how best to include both of these elements in a single training programme. It is common practice among athletes, coaches and recreational exercisers to perform a stretching routine before a strength training session. Stretching exercises are regularly recommended, even in many textbooks, with the claimed purpose of preventing injury and muscle soreness, or even enhancing performance. However, as highlighted in recent review articles, this recommendation lacks scientific evidence. Thus, the purpose of the present review is to determine the acute and chronic effects of stretching on strength performance, together with the underlying mechanisms. Although most studies have found acute decreases in strength following stretching, and that such decreases seem to be more prominent the longer the stretching protocol, the number of exercises and sets, and the duration of each set have, in general, exceeded the ranges normally recommended in the literature. Consequently, the duration of the stimuli were excessively long compared with common practice, thus making evident the need for further studies. In addition, when recommending flexibility exercises, one should consider other underlying issues, such as the safety of the participants, possible increases in injury risks and the unnecessary time expenditure. Many mechanisms underlying stretching exercises still demand investigation so that links between the observed effects, their causes and the consequences may be constructed.